2017
DOI: 10.1016/j.solener.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A general method to analyze the thermal performance of multi-cavity concentrating solar power receivers

Abstract: Concentrating solar power (CSP) with thermal energy storage has potential to provide grid-scale, on-10 demand, dispatachable renewable energy. As higher solar receiver output temperatures are necessary for 11 higher thermal cycle efficiency, current CSP research is focused on high outlet temperature and high 12 efficiency receivers. The objective of this study is to provide a simplified model to analyze the thermal 13 efficiency of multi-cavity concentrating solar power receivers. The model calculates an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Recently, many studies have been conducted on solar tower systems [5][6][7], Stirling engines [8,9], Fresnel lenses [10][11][12] and solar Brayton cycle enhancement [13][14][15]. Furthermore, several studies on the heat losses and the receivers' geometries, dimensions and positions are found in [16][17][18][19][20][21][22][23]. For instance, the combined convection and radiation of a modified hemispherical cavity receiver with fins used with solar parabolic dish was numerically analysed by Ngo et al [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have been conducted on solar tower systems [5][6][7], Stirling engines [8,9], Fresnel lenses [10][11][12] and solar Brayton cycle enhancement [13][14][15]. Furthermore, several studies on the heat losses and the receivers' geometries, dimensions and positions are found in [16][17][18][19][20][21][22][23]. For instance, the combined convection and radiation of a modified hemispherical cavity receiver with fins used with solar parabolic dish was numerically analysed by Ngo et al [16].…”
mentioning
confidence: 99%
“…Moreover, for the same given total heat input, the region closer to the cavity aperture experienced larger view factors and as a result, larger radiation loss. The thermal performance of multi-cavity concentration was analysed by Austin et al [19]. Intensive studies on the thermal analysis of cavity receivers for parabolic dish application were achieved by Reddy and Kumar [20][21][22][23].…”
mentioning
confidence: 99%
“…Also, deviation between theoretical and the experimental results ranged between 2.5 % to 8%. A model of multi-cavity receiver for high concentrated flux was analysed by Fleming et al [29]. The study was carried out on a simple model designed with all the necessary parameters for analysing its thermal efficiency by applying an optimal value and distribution of flux.…”
mentioning
confidence: 99%
“…As reported in the RPPR2, in the SunShot Particle Receiver Project, NREL and its partners published or submitted 13 papers, including papers listed in references [12][13][14][16][17][18]. NREL filed three U.S. patents that cover the particle-TES design and construction, heat exchanger configuration for steam, s-CO2, and air-Brayton power DE-EE0001586 Near-Blackbody Enclosed Particle Receiver NREL, Zhiwen Ma, PI provides utility-scale electricity storage capacity and could greatly improve the reliability and grid stability of renewable power generation.…”
Section: Intellectual Property Outcome and Technology Development Pathmentioning
confidence: 99%